PERENCANAAN STRATEGIS TEKNOLOGI INFORMASI PERPUSTAKAAN UNIVERSITAS TRISAKTI - Sri Handayani, Diah (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2013)
The very fast development of information technology has brought many changes to university libraries. Libraries should be able to deal with those changes by implementing appropriate strategy, otherwise it would be neglected by its users. Using SWOT and IT Balanced Scorecard qualitative approach, this study aims to result in information technology strategic planning implemented in Usakti Library. This study showed that the internal condition of Usakti Library is within average category. Meanwhile the external condition is in a medium category. The SWOT analysis resulted in ten strategies. For each strategy, measurement, target and its initiative strategy was set. The user orientation perspective is in the highest priority by 30.6% score and its main strategy is to improve the usage and quality of information technology-based services for user satisfaction scored 38.9%.